Acute phase proteins in patients with head and neck cancer - Stasik, Zofia; Tarapacz, Jadwiga; Migas, Beata; Skołyszewski, Jan (Contemporary Oncology/Współczesna Onkologia, 2006)
The determination of acute phase proteins such as albumin, prealbumin, alpha-1 acid glycoprotein, alpha-1 antitrypsin, transferrin, C-reactive protein and also calculation of coefficients such as CSI, CRP/PRE and PINI were performed in the group of 33 patients with squamous cell carcinoma of the pharynx and larynx stage T 1–4 N 0–3 M 0 , before radiotherapy. One year after treatment, the determined factors were analysed in respect to clinical performance of patients. In the group of patients with symptoms of disease progression, in comparison to others, hypoalbuminemia and an elevated value of PINI were frequently observed before treatment.